2022
DOI: 10.1038/s41467-022-33476-6
|View full text |Cite|
|
Sign up to set email alerts
|

Self-organization of an inhomogeneous memristive hardware for sequence learning

Abstract: Learning is a fundamental component of creating intelligent machines. Biological intelligence orchestrates synaptic and neuronal learning at multiple time scales to self-organize populations of neurons for solving complex tasks. Inspired by this, we design and experimentally demonstrate an adaptive hardware architecture Memristive Self-organizing Spiking Recurrent Neural Network (MEMSORN). MEMSORN incorporates resistive memory (RRAM) in its synapses and neurons which configure their state based on Hebbian and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Similarly, another powerful plasticity mechanism inspired by nature that is fundamental for improving robustness and stability, is that of homemostatic plasticity [119,120]. Electronic implementations of homeostatic plasticity mechanisms have been proposed using both pure CMOS [98,99,121] and hybrid memristive/CMOS [122][123][124] technologies.…”
Section: Using Spike-based Learning and Plasticitymentioning
confidence: 99%
“…Similarly, another powerful plasticity mechanism inspired by nature that is fundamental for improving robustness and stability, is that of homemostatic plasticity [119,120]. Electronic implementations of homeostatic plasticity mechanisms have been proposed using both pure CMOS [98,99,121] and hybrid memristive/CMOS [122][123][124] technologies.…”
Section: Using Spike-based Learning and Plasticitymentioning
confidence: 99%
“…A second strongly related work is the MEMSORN network by Payvand et al (2022). Here, a memristive crossbar array recurrently connects LIF neurons to perform sequence learning tasks in a Spiking RNN (SRNN).…”
Section: Relation To Previous Workmentioning
confidence: 99%
“…There are a number of biologically motivated sequence learning models that are closely related to the spiking TM, such as the self-organizing recurrent neural network model (SORN, Lazar et al 2009). Recent work incorporated memristive dynamics into the synapses and neurons of the SORN model and showed that it retains successful performance (Payvand et al 2022). The authors studied the role of variability and showed that it can improve the prediction performance.…”
Section: Relationship To Previous Modelsmentioning
confidence: 99%